The Space Resource Exploration and Utilization Act: A move forward or a step back?. (November 2015) - Tronchetti, Fabio
Abstract: On May 21, 2015, the US House of Representatives passed a revised version of the ASTEROIDS Act, now labeled the Space Resource Exploration ad Utilization Act. If endorsed also by the US Senate the Act may be formally enacted into law by the President of the United States. In the light of this important development it seems appropriate to analyze the content and the legal and political implications of the Space Resource Exploration and Utilization Act.